Factors associated to perceived stress in hospital workers in a psychiatric hospital in Spain during COVID-19 - CB Avella-Garcia; R Salvador; D Paiva; A Martinez-Muelas; A Magariño; S Pérez; M Vergel; A Ayala; T Baena; J Gómez; M Sánchez (Psicosomática y Psiquiatría, 2021)
Background: Health workers enduring the COVID-19 pandemic could be at risk of psychological stress. This study aimed to 1) measure the levels of perceived stress by workers at a psychiatric hospital in Barcelona, Spain, 2) to identify demographic or occupational factors related to a higher risk of perceiving greater stress, and